Inculcating Leadership Values for the Student Council of University In The University of Darussalam Gontor - Khairul Umam; Sutama Sutama (Educan : Jurnal Pendidikan Islam, 2021)
The leadership of leader is very important for organization because they will determine the organization through the decisions he makes. Leadership values can be inculcated through the organization, including student organizations. As a pesantren university, the student council of University of Darussalam Gontor plays an important role in student activities during the education process. The purpose of this study is to know the inculcation of leadership values for the management of the student council in University of Darussalam Gontor. The research method used qualitative research with the research subject is the supervisor and administrator of student council of University of Darussalam Gontor. Data collection techniques in this study were interviews, observation and documentation. The results of the study indicate that there are several methods to inculcate leadership values in the student council organization of University of Darussalam Gontor, including: 1. Guidance and training of briefing and training activities are given to the student council with the aim of the student council management having high dedication and integrity to the organization they live in, 2. Assignments and Habituation applied to the management of the student council of Darussalam Gontor University so that they are accustomed to leading then they are given the responsibility to lead activities, 3. Escort All tasks and activities given to the management must receive guidance and assistance, so that all what has been programmed is controlled, evaluated and directly known, in this case the student council always holds regular meetings with the supervisor.